Study on the Mechanism of Rapid oil-water separation by Fe3O4 @PMMA@PDMS intelligent super hydrophobic micro/Nano robot in Indian context (International Journal of Food and Nutritional Sciences, 2022)
The development of a new superhydrophobic magnetic melamine sponge (PDMS@Fe3O4/MS) for effective oil-water separation is presented in the paper. A modified melamine sponge, polydopamine sheath, and nano-Fe3O4 particles combine to form a unique superhydrophobic advanced material with a liquid contact angle of 150.9°. The modified sponge exposes a liquid, which is uniquely revealed. Scanning electron microscopy (SEM) characteristics show structural changes throughout the process. X-ray diffraction (XRD) analysis shows that the presence of nano-Fe3O4 does not cause the melamine sponge to produce distinctive diffraction peaks and also confirms that the sponge is well coated with PDMS. According to Fourier transform infrared spectroscopy (FTIR), oxygenated functional reducing groups appear on the PDMS@Fe3O4/MS surface, enhancing its hydrophobicity and lipophilicity. The study of oil adsorption capacity shows that PDMS@Fe3O4/MS can absorb various oils. Due to the three-dimensional porosity of the sponge and the combined water repellent properties of the PDMS, the material shows remarkable oil and water separation efficiency up to 99.34%. Performance tests show that the material can go through several cycles of oil absorption and deoiling, but the rate of absorption and wear gradually decreases. The nano-Fe3O4-enhanced magnetic reactivity of the sponge allows magnetic fields to be used for efficient handling and recycling.